An Analysis On Framing The News Of Lash Punishment On Gay In Aceh In Serambi Indonesia Daily Newspaper - Zuniadi, Ilham (JURNAL SIMBOLIKA: Research and Learning in Communication Study, 2018)
The purpose of this study was to analyze Serambi Indonesia Daily in framing and producing news that occurred in the editorial room as well as the construction of reality in reporting foreign intervention in cases of caning against gay perpetrators. Through a practical analysis discourse. seen from five levels that influence media content by Shoemaker Reese. Qualitative methods with a constructivist paradigm are used to pay attention to the politics of meaning and the process of how a person makes a picture of reality that influences the stereotypes that develop in society. Framing analysis of Robert N. Entman's model is used to see the frame of two major dimensions, namely the selection of issues and the prominence of certain aspects of the issue. The result of the research shows that Serambi Indonesia Daily Newspaper, in its news about lash punishment on gays in Aceh always considers local values in Acehnese community that are Moslems so that the frame for lash punishment is considered as the legal problem in which the gays are considered violating against Qanun No. 6/2014 on Jinayah Law.